IMPLEMENTATION OF CHARACTER EDUCATION IN BUILDING SCHOOL CULTURE - Aunurrahman Aunurrahman (Universitas Tanjungpura, 2021)
This research aims to find out about the implementation of character education in building school culture. The research was conducted at elementary schools in Sambas Regency with representation of a number of elementary schools from several sub-districts in Sambas Regency. The data were collected by combining quantitative and qualitative approaches, with data collection techniques using interviews, FGDs and questionnaires. The qualitative data analysis used the interactive analysis technique of Miles and Huberman, while the quantitative data analysis used factor analysis and percentage. The results showed that in general the implementation of character education in building school culture in the Sambas Regency elementary schools in several dimensions was well implemented. However, in certain parts, especially in the dimensions of the program and evaluation, it has not been fully actualized as expected. Meanwhile, school culture as a whole has developed well, especially in the dimensions of disciplinary culture, exemplary culture and culture of order and cleanliness. These three dimensions of culture are the fundamental foundation of building school culture. In the disciplinary culture dimension, the biggest contribution is to hold the midday prayer in congregation, while in the dimension of order and cleanliness culture, the biggest contribution is to hold a school ceremony.Key words: Character Education, School Culture